Análisis del riesgo crediticio de la cooperativa de ahorro y crédito la libertad 3, que se encuentra ubicada en la provincia de Cotopaxi, cantón Latacunga, parroquia Pastocalle durante el período enero – diciembre del 2011 para determinar la situación financiera - Benites Guato, María del Carmen (2015)
This research present has as purpose to perform an analysis of the financial situation the Cooperative of Saving and Credit La Libertad 3 it is located in Cotopaxi province, through the use of financial statements, financial indicators for to know the real situation in which it is located and to provide information that enables it to be one of the best cooperatives. To develop the work was necessary to make a study of the economic structure of the cooperative where the type of research that was applied field, the same that originated in the scene allowing direct contact with the entity, for this purpose was used descriptive methods….